Molecular Characterization of Fish Species Using Mitochondrial DNA 12S rRNA. - Ferdaus, Fatin Soleha (Universiti Sains Malaysia, 2015)
This study was undertaken to study the capability of a set of new primers (unpublished) to amplify partial sequence of mitochondrial DNA (mtDNA) 12S rRNA gene of marine and freshwater fish species. The primers namely Forward: 5’ - CAA ACT GGG ATT AGA TAC CCC AC - 3’, and Reverse: 5’ - TAC RCT TAC CAT GTT ACG ACT T - 3’ were able to amplify the seventeen fish species chosen for this study. Pairwise comparison of the sequence data of the 17 fish species were undertaken to study the intra-species variations in the partial sequence of mtDNA 12S rRNA gene. The Thunnus tonggol and Scomberomorus commerson showed the highest similarity that is 89.37%. Diagramma pictum and Siganus canaliculatus showed the second highest similarity with 86.26%. The lowest similarity seen between Leptobarbus hoevenii and Nemipterus bathybius with 67.77%. A total of 1354 nucleotide positional polymorphisms were recorded. The transition (T<->C and A<->G) 628 out of 1354 and the number of transversion was 514. The lowest number of nucleotide polymorphism was observed in Siganus canaliculatus 8.3% and Nemipterus bathybius has showed the highest nucleotide polymorphism with 26.81%. An unrooted neighbor joining tree (NJ) was constructed to study their genetic relationship.